Yaws elimination in Ecuador: Findings of a serological survey of children in Esmeraldas province to evaluate interruption of transmission - Philip J. Cooper; Mariella Anselmi; Cintia Caicedo; Andrea Lopez; Yosselin Vicuña; Jaen Cagua Ordoñez; Julio Rivera Bonilla; Alejandro Rodriguez; Aida Soto; Angel Guevara (Public Library of Science (PLoS), 2022)
Background The WHO roadmap for neglected tropical diseases includes yaws eradication requiring certification of elimination of transmission in all endemic and formerly endemic countries worldwide. A community-based programme for yaws control was considered to have achieved elimination of the infection in the endemic focus in Ecuador after 1993. We did a serosurvey of children in this focus to provide evidence for interruption of transmission. Methods Survey of serum samples collected from children aged 2 to 15 years living in the formerly endemic and in geographically contiguous areas. A convenience sample of sera collected between 2005 were 2017 from non-yaws studies, were analyzed using immunochromatic rapid tests to screen (OnSite Syphilis Ab Combo Rapid Test) for Treponema pallidum-specific antibodies and confirm (DPP Syphilis Screen and Confirm) seroreactivity based on the presence antibodies to treponemal and non-treponemal antigens. Results Seroreactivity was confirmed in 6 (0.14%, 95% CI 0.06-0.30) of 4,432 sera analyzed and was similar in formerly endemic (0.11%, (95% CI 0.01-0.75) and non-endemic (0.14%, 95% CI 0.06-0.34) communities. All seroreactors were of Afro-Ecuadorian ethnicity and most were male (4/6) and aged 10 or more years (5/6), the latter possibly indicating venereal syphilis. Only 1 seroreactor lived in a community in the Rio Santiago, that was formerly hyperendemic for yaws. Conclusion We observed very low levels of treponemal transmission in both formerly endemic and non-endemic communities which might be indicative of congenital or venereal syphilis and, if yaws, would likely be insufficient to maintain transmission of this endemic childhood infection. Additional surveys of children aged 1 to 5 years are planned in Rio Santiago communities to exclude yaws transmission. Author summary Yaws, caused by infection with the spirochete, Treponema pallidum pertenue, causes a chronic debilitating condition of skin, cartilage, and bone, and is transmitted during childhood through skin-to-skin contact. Yaws has been targeted for eradication as part of the WHO roadmap for control of neglected tropical diseases, requiring certification of elimination in all endemic and formerly endemic regions. Yaws in Ecuador has been restricted to a geographically isolated focus in a rainforest region of Esmeraldas Province in northern coastal Ecuador. Following a strategy of repeated 5-yearly clinical and serological surveys with mass-treatment and surveillance between surveys, yaws was assumed to have been eliminated by 1998. To provide the evidence base to certify the elimination of transmission in Ecuador, this study presents an analysis of stored sera collected from 4,432 children between 2005 and 2017 from formerly endemic and non-endemic communities. Screening and confirmation of seroreactors was done using two validated rapid tests for T. pallidum. Seroreactivity was observed in 6 samples (0.14%) and was similar in formerly endemic (0.11%) and non-endemic (0.14%) communities, possibly explained by background rates of congenital or venereal syphilis. Only 1 active infection was detected in formerly endemic communities. To our knowledge, this is the first study of yaws from the Americas to evaluate the elimination of transmission. Our data indicate that active yaws transmission is unlikely to be occurring in formerly endemic communities. Additional surveys of young children may be required to confirm interruption of transmission.